Rehabilitation of the damaged brick infilled RC frames by CFRP overlays and epoxy injection - Karataş, Ozan. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
The effect of damage and comparison with the undamaged specimen considering the engineering properties (stiffness, strength, energy dissipation, ductility…etc.) of infilled RC frames with or without CFRP were evaluated experimentally and analytically. Two single-bay, two-story damaged specimens at 1/3 scale were tested in a vertical position under quasi-static reversed cyclic seismic loading. Vertical and lateral loads were applied concurrently. These specimens were strengthened with CFRP unidirectional overlays in various configurations and the cracks were repaired with epoxy injection. The specimens had some deficiencies commonly seen in pre-1998 Turkish construction. The specimens had detailing deficiencies; such as insufficient confinement, 900 hooks, no transverse reinforcement in the joints, design deficiencies; such as weak column-strong beam, and construction deficiencies; such as poor material quality, and inadequate lap splice length. They also had different damage levels and aspect ratio which was tested under same circumstances by Atmaca in 2008. To eliminate the existing deficiencies and capacity loss due to the damage and cracks, unidirectional CFRP overlays were applied in the form of vertical strips and/or cross diagonals on both sides of the infill panel and anchored to the surrounding RC frames. The brick loss were repaired and the cracks were filled with epoxy. The application of CFRP overlays and epoxy injection improved the load carrying capacity and the energy dissipation capacity of damaged specimen, close to the undamaged strengthened condition. Generally, as the peak loads increased, their corresponding drifts also increased and the general behavior of damaged specimens were approximately same with the one Atmaca’s experimental undamaged specimens. Some stiffness improvements were also recorded depending on damage level and the aspect ratio of the frames. The experimental capacity of the specimens was compared with both analytical calculation and experimental values of the Atmaca’s undamaged strengthened specimens with same conditions.
Keywords: Reinforced plastics.; Fiber-reinforced plastics.; Epoxy resins.